Institutional Relationship Model to Realize a Sustainable Tourism Management in Pulau Merah Banyuwangi - Rita Parmawati; Wike Wike; Farida Nurani; Rizha Hardyansah (Journal of Indonesian Tourism and Development Studies, 2021)
Pulau Merah Beach must have sustainable tourism management that involves many institutions in the regional area as decision-makers and controls the regional plan. This research aims to analyze the institutional sector for tourism management on Pulau Merah Beach to support sustainability. Data were obtained through interviews with the Head of BAPPEDA, the Head of the Culture and Tourism Office, Spatial Planning Practitioners, Environmental Experts, and Local Communities. Data then analyzed with Interpretive Structural Modeling (ISM). There are four elements used to measure the institutional tourism management in Pulau Merah Beach, i.e. (1) elements of institutional (20 sub-elements); (2) elements of institutional problems (12 sub-elements); (3) elements of expected goals (11 sub-elements); (4) elements of the required program (11 sub-elements). The results of the analysis conducted show that DISBUDPAR is an institution with a role and authority in regulating tourism on Pulau Merah Beach, but it requires cooperation with other agencies to achieve sustainable management. The expected goals of tourism management in Pulau Merah Beach are sustainable, integrated, synergy, efficient, and sufficient, and firm law enforcement. However, there is no clear SOP between institutions. So, it can lead to a lack of integration between institutions and the emergence of unclear standards and measuring instruments. To achieve goals and resolve existing problems, designing several programs is required, such as forming a specific institution that handles the tourism management of Pulau Merah Beach, evaluating policies, and integrating tourism management's technical guidelines in the Pulau Merah Beach Area. If each key point can be optimized, it will be possible to realize sustainable tourism management on Pulau Merah Beach Banyuwangi.Keywords: DISBUDPAR, institution, interpretive structural modelling, sustainable tourism.